Dispersal limitation dominates the community assembly of abundant and rare fungi in dryland montane forests - Wang, Jianming; Wang, Yin; Qu, Mengjun; Li, Jingwen (Frontiers in Microbiology, 2022)
The assembly mechanisms and drivers of abundant and rare fungi in dryland montane forest soils remain underexplored. Here, we compared the distribution patterns of abundant and rare fungi, and explored the factors determining their assembly processes in a dryland montane forest of China. Stronger distance-decay relationships were found in abundant sub-communities than in rare sub-communities. In addition, abundant fungi exhibited greater presence and wider habitat niche breadth than rare fungi. Null model and variation partitioning analysis indicated that dispersal limitation and environmental selection work together to govern both abundant and rare fungal assembly, while dispersal limitation plays a dominate role. Meanwhile, the relative influence of dispersal limitation and environmental selection varied between abundant and rare sub-communities, where dispersal limitation showed greater dominance in abundant fungal assembly. Mantel tests demonstrated that soil pH and phosphorus played critical roles in mediating the assembly processes of abundant and rare fungi, respectively. Our findings highlight the distinct biogeographic patterns of abundant and rare fungi are driven by different assembly mechanisms, and the assembly processes of abundant and rare fungi are determined by diverse ecological drivers in dryland montane forest soils.